PENGARUH PENGGUNAAN MEDIA PADLET TERHADAP AKTIVITAS BELAJAR SISWA GEOGRAFI FASE E DI SMAN 2 BATANG ANAI - Anindita Sasikirana; Ernawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of using Padlet media on student learning activities in learning Geography in Phase E at SMAN 2 Batang Anai. The background of this research is based on the low involvement of students in the conventional learning process that tends to be monotonous and minimal media innovation. Padlet media, as an interactive digital platform, is expected to create a collaborative, fun learning atmosphere, and increase students' active participation. The method used in this research is quasi experiment with pretest-posttest control group design. The research sample consisted of two classes, namely the experimental class using Padlet media and the control class using the lecture method. Data collection techniques were conducted through student learning activity questionnaires, observation, and documentation. The instruments were tested for validity and reliability before being used in the research. The results of the analysis showed a significant difference in the level of student learning activities between the experimental and control classes. The learning activities of students who used Padlet media increased significantly compared to students who did not use the media. This proves that the use of Padlet media has a positive effect on increasing student learning activities in Geography subjects. This study concludes that Padlet media can be an effective alternative in increasing students' learning activities and is recommended to be applied more widely in digital-based learning in schools.